Implementasi Pendidikan Finansial Sejak Dini Melalui Pengelolaan Uang THR - Bandawaty, Euis; Sunaryo, Sunaryo; Meindro, Meindro; Herawati, Heny; Sanjoyo, Sanjoyo; Suldina, Farida (Gapenas Publisher, 2022)
This community service aims to train and implement financial education from an early age through the management of Holiday Allowances (THR) for children in Sukasetia Village. The method used is collaboration with participators involving a series of interactive activities such as educational games, financial simulations and discussions. The results of community service activities show that direct and practical financial education has succeeded in improving children's financial understanding and behavior. Children are enthusiastic and happy in wanting to save, and can make wise financial management decisions. From the results of the briefing and simulation provided by the community service team, it is suggested that a contextual educational approach, involving the active participation of parents, is effective in developing children's financial literacy. The conclusion of this community service emphasizes the importance of financial education from an early age to prepare children to face economic challenges in the future. It is recommended that this financial education program be implemented more widely, especially in rural communities, to increase financial literacy nationally.